Avaliação dos impactos ambientais de processos oxidativos avançados na remoção de micropoluentes e ecotoxicidade - Ramos, Heitor de Oliveira (2022)
Advanced oxidation processes (AOPs) have been shown to be efficient in the degradation and removal of micropollutants (Mps) in effluents. On the other hand, little is discussed about the performance and environmental impacts that these processes can generate when treating these effluents. Life Cycle Assessment (LCA) has proved to be an important tool to assist in decision making regarding the best treatment alternative, taking into account its potential environmental impacts. In this context, the present project evaluated the environmental impacts of three processes (photolysis UVC, UVC/H2O2 and photo-Fenton/UVA) that were used as tertiary treatment of synthetic domestic effluent, with the objective of removing micropollutants and ecotoxicity. LCA was used as a tool for this comparative study. Three different scenarios were stipulated: a) anaerobic process + photolysis/UVC; b) anaerobic process + UVC/H2O2 process and c) anaerobic process + photo-Fenton process. The functional unit chosen for comparison purposes was 1 m³ of treated synthetic effluent. The inputs and outputs were determined and from that, the inventory was established considering the treatment times of 30, 60 and 90 min. The inventory analysis revealed that of the three analyzed processes, the UVC/H2O2 process contributed the least to the analyzed impact categories. Photolysis was the process that most contributed to the impacts in the categories Freshwater Ecotoxicity, Human Toxicity (noncarcinogenic) and Human Toxicity (carcinogenic). The photo-Fenton process was the one that most contributed to the impacts in the categories related to the increase in global warming (IPCC GWP 20a and IPCC GWP 100a) and Marine Eutrophication. Regarding the greater efficiency in the removal of PMs, total organic carbon and ecotoxicity to Daphnia magna and Lactuca sativa, the photo-Fenton process showed the best performance. There was no significant difference regarding the treatment times of each process (30, 60 and 90 min). Finally, the lack of ecotoxicity and human toxicity characterizing factors is in part due to a lack of toxicity test data, especially chronic toxicity assays for many organic compounds. As micropollutants are present in the environment at low concentrations (ng to ug/L), chronic effects must be monitored. This information must be constantly added to databases, such as USEtox, só that they are updated and this makes the impact assessment closer to reality.